Pengembangan Media Interaktif Berbasis Augmented Reality dalam Model Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik SMAN 16 Makassar - Sahrawati, Fiska; Muharram, Muharram; Sulastry, Taty (Program Pasca Sarjana UNM, 2023)
This study is a development research that aims to produce interactive media based on augmented reality in a valid, practical, and effective discovery learning model. The development model used is the ADDIE development model which consists of five stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The interactive media based on augmented reality that was developed was validated by two experts. Then, it was tested to 40 students in grade X MIA 7 at SMAN 16 Makassar. The results of the study reveal that the developed interactive media based on augmented reality meets the criteria of validity, practicality, and effectiveness. The interactive media based on augmented reality is stated to be valid based on the results of validating interactive media based on augmented reality with an average value of the media expert and material expert of 3.78 and 3.77, which are in very valid category. The interactive media based on augmented reality is stated to be practical based on (1) the implementation of interactive media with an average total percentage of 96.56%, which is in very high category; (2) the teacher's response with an average score of 93.37%, which is in very practical category; and (3) the students’ responses with an average score of 89%, which is in very practical category. The interactive media is stated to be effective based on the results of the analysis of the learning outcomes test and analysis of learning motivation questionnaires with a class completeness percentage of 90% and an average value of the percentage of learning motivation assessment of 90%, which is in very high category. Therefore, the results of the study indicate that interactive media based on augmented reality in the discovery learning model has valid, practical, and effective qualities.